Personagens femininas em "Deus de Caim" de Ricardo Guilherme Dicke : corpo e violência - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The aim of this analysis is to address how the bodies of female characters are exposed and represented in “Deus de Cain”, by Ricardo Guilherme Dicke. It is noticed, in Dickean writing, themes that are recurrent, those linked to human nature is one of them. In view of this, we sought to highlight how women are written in this narrative, with a view to representing their bodies. Therefore, the narrative strategies employed by the author to portray the characters based on their characteristics, actions and situations experienced by them were analyzed. The woman is represented in the Dickean novel from different situations, violence is one of them. In these scenes, their bodies are exposed to violent practices, such as rape. There is also the presence of the questioning, reflective woman, Irene, and the one who dared to go against traditional social standards, Rosa. Thus, it is noted that Ricardo Guilherme Dicke portrays images linked to the female body through different perspectives, from the construction of portraits of violence practiced against these bodies to scenes that expose women in an active and autonomous position. In these constructions, Dicke provokes reflections, questions about oppressive practices that prevail in different social contexts. In this way, the novel emphasizes the complexity of experiences lived by the characters, promoting the discovery of their behaviors and intimacies and, at the same time, reveals subtle mechanisms of resistance, or not, of these women. In this regard, it is possible to reflect and question the circumstances in which the female body is exposed, the forms of repression and resistance in different social spaces. To theoretically support this study, a dialogue was sought with theorists and critics who deal with the position of women in society, it is worth mentioning some of them: Beauvoir (1970), Bourdieu (2012), Del Priore (2010) and (2020), Grosz (2000), Louzada (2019), Matos; Soihet (2003), Perrot (1989), (2005) and (2019), Saffioti (2004), Saffioti and Almeida (1995), and Xavier (2007).
Female characters in "Deus de Cain" by Ricardo Guilherme Dicke : body and violence
Keywords: Ricardo Guilherme Dicke; Deus de Caim; Corpo; Mulher - personagem; Violência; Character; God of Cain; Body; Woman - character; Violence; LETRAS::LITERATURA BRASILEIRA